(3JgPjH GdcdGe aj JMQjQ GdefWb hGdcdGes - (3GdJaJGRGfj, SYO GdOjf, eSYhO Hf YeQ Hf YHO Gddg, J(B793(3g`s ((3eMeO QMje Hf edG YHO GdbGOQ GdeMQQs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj gOGfG ShGA GdWQjb hHYO agPG ZGjI JgPjH GdcdGe aj JMQjQ GdefWb hGdcdGe hJbQjH GdeQGe ef JbQjQ YbGFO GdESdGe s
(3BNQgG (B:s
(3hGdJMOjO Cj aYd GdMO hGdHQgGf Cj GdWQjb Edi Gdhbha Ydi GdMb hGdYed Hg CTHg HGdebGUOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7 / 219s
(3eYLe GdeDdajf (B3 / 849s
(3cTa GdXfhf (B1/515s
(3TPQGJ GdPgH (B6 / 319s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs